Legal Protection for Directors Through the Business Judgment Rule in the Acquisition Case of PT Jalan Nusantara - Dimas Adhitia; Sodikin Sodikin (Interdisciplinary Social Studies, 2025)
The Business Judgment Rule (BJR) is a corporate law principle that provides protection to directors for business decisions taken in good faith, prudence, and orientation to the interests of the company. This concept becomes important when the directors' decisions result in losses or alleged criminal acts, as occurred in the case of the acquisition of PT Jalan Nusantara (JNT) by PT ASDP Indonesia Ferry (Persero) which involved three former directors of the company. The problem is how the Business Judgment Rule (BJR) can provide legal protection to directors in the strategic decision-making process, as well as assessing the limitations and exceptions to its application if there are indications of abuse of authority, serious negligence, or conflicts of interest. By using a normative juridical approach and analysis of court decisions, laws and regulations, and corporate law literature, this study shows that the application of the Business Judgment Rule (BJR) requires proof that the directors acted in accordance with fiduciary duty standards, including the duty of care and duty of loyalty. The research findings confirm that the Business Judgment Rule (BJR) cannot be used as a shield if acquisition decisions are made without adequate feasibility studies, deviate from corporate procedures, or carry the potential for state losses. Therefore, this contribution contributes to understanding the limits of legal protection for state-owned enterprise directors and its legal implications for corporate decision-making practices in Indonesia.